Pilot study of safety and efficacy of polyprenols in combination with coenzyme Q10 in patients with statin-induced myopathy - Gustavs Latkovskis; Vita Saripo; Emma Sokolova; Dana Upite; Ilona Vanaga; Ugis Kletnieks; Andrejs Erglis (Medicina, 2016)
Background and objective: Statin-induced myopathy (SIM) has been partially attributed to deficiency of dolichol and coenzyme Q10 (CoQ10). We aimed to test the safety and efficacy of plant polyprenols in combination with CoQ10 for alleviation of SIM. Materials and methods: In an open-label, one-center prospective pilot study patients with SIM received conifer-tree needle polyprenols (4 mg/day) and CoQ10 (100 mg/day) for 8 weeks. Symptoms and safety were evaluated according to symptom severity score (0–10), creatine kinase (CK) levels, exercise test, dynamometry, complete blood count, clinical biochemistry and electrocardiography. Results: Of the 14 patients, 11 completed the study per protocol. Two patients withdrew consent due to travels abroad, and it was discontinued for one patient with stage 3 chronic kidney disease due to asymptomatic elevations of liver enzymes at week 4. No safety parameters changed significantly in per protocol group. Non-significant increase of CK levels was observed (P = 0.231). Muscle pain (n = 10) and weakness (n = 7) scores improved significantly (P < 0.001 and P = 0.018, respectively). Muscle pain completely disappeared in 2 patients, weakness resolved in 3 patients and cramps disappeared in two patients. Four patients assessed improvement strong enough to consider increase of statin dose. No changes were observed in exercise test or dynamometry. Conclusions: Conifer-tree polyprenols in combination with CoQ10 may be generally safe in patients with SIM, but caution should be exercised in patients with glomerular filtration rate <60 mL/min and routine monitoring of the liver enzymes and CK is advocated in all patients. The observed efficacy provides the rationale for a larger, double-blind controlled study with polyprenols.